PANCASILA DAN HAK ASASI MANUSIA : MENJAGA KESEIMBANGAN ANTARA HAK INDIVIDU DAN KEPENTINGAN UMUM - Junaedi, Oding (LEX OMNIBUS : Jurnal Hukum Tata Negara dan Administrasi Negara, 2024)
This article discusses the balance between individual rights and public interest in the context of human rights based on the principles of Pancasila. Human rights are recognized in the Indonesian legal system, but their implementation takes into account social harmony. This study uses a normative method with a legislative and conceptual approach. The results of the study indicate that Pancasila is the basis for balancing individual freedom with social responsibility. However, challenges arise in implementation, especially related to freedom of expression, public policy, and social justice. Several regulations, such as the ITE Law and spatial planning policies, reflect the state's efforts to regulate this balance, although they still need to be evaluated to avoid excessive restrictions on individual rights. This study emphasizes that human rights in the Indonesian legal system are not absolute, but must be in line with the values ​​of Pancasila. Therefore, it is necessary to revise policies that have the potential to disproportionately limit individual rights and strengthen public understanding of human rights within the framework of Pancasila.